Buddhist approaches to counselling and psychotherapy:Exploratory discussions from different traditions - Ng, Alvin Lai Oon *; Hon, Ee Mun; Chia, Ming Tik (Medical Information Science Reference, 2019)
Three authors from differing Buddhist backgrounds share their approaches to using Buddhism in psychotherapy. The authors argue that Buddhism itself is fundamentally a psychotherapy approach because it is essentially a prescription to end discontent and misery. This chapter provides basic points on how Buddhism can be used in counselling by discussing how different Buddhist traditions might approach counselling. This chapter also brings up reflections on how practice may differ according to experience in the fields of counselling and clinical psychology. Overall, the chapter is subdivided into six parts: (1) introduction; (2) basic tenets of Buddhism relevant to psychotherapy; (3) case study illustrations of applied Buddhism in counselling and psychotherapy; (4) discussion on reconciling differing Buddhist schools of thought in the practice of counselling and psychotherapy; (5) discussion on compatibility of Buddhist principles with applied Western philosophies and therapeutic approaches; and (6) suggestions of future directions given the current research literature patterns.